Pelatihan Digitalisasi Sistem Informasi Manajemen Pelayanan Geraja Di Wilayah GMIT Klasis Kota Kupang Timur - Alya Elita Sjioen; Jofret Umbu Soru Peku Djawang; Mefibosed Radjah Pono; Gregorius Rinduh Iriane; Febriyana Tumewu; Junita Israhel Dethan; Febriyani Tumewu; Riyandis Braen Tubulau (Universitas 45 Surabaya, 2023)
Management information systems in church services are also a necessity. One of the organizations that need information technology to support ministry is the church, in this case the churches that are in the GMIT Kalasis service area, East Kupang City. Each of the churches that are in the service of the Klass terrorist in East Kupang City has various information such as church profiles, assembly and congregation data, worship schedules, church financial information, articles and other information. Service information at the church is still not optimal because it is only limited to news from church pulpits and social media. The church service management information system which is still manual, namely by using Microsoft Office and the number of documents stored in the form of physical archives or printed documents such as church member registration documents, mourning, baptism, and marriage still uses data collection forms. System like this is less effective because it can make it difficult for church staff in archiving or searching data and is less efficient because it requires quite large operational costs in each year's service budget. Through this activity the results achieved were providing education so that the church could utilize a website-based management information system that can be installed on Android for the church to have as an effective means of information to support church services to congregations and design a management information system needed by the church in support of church ministry.